(untitled) (Journal of the College of Basic Education, 2022)
Many scientists and strategic experts describe the current era as the era of the information revolution, which is characterized by the telecommunications revolution, remote sensing, and geographic information systems that can provide, transfer and analyze important information and data in real time to support decision makers in many important decisions that require accuracy and speed. And the credibility of the data and information under study, and information systems in general and geographic information systems in particular are among the important tools that institutions, agencies and organizations working in the field of decision-making support seek.